Detection of Abundant Non-Haematopoietic Circulating Cancer-Related Cells in Patients with Advanced Epithelial Ovarian Cancer - Kumar, Juhi; Chudasama, Dimple; Roberts, Charlotte; Kubista, Mikael; Sjöback, Robert; Chatterjee, Jayanta; Anikin, Vladimir; Karteris, Emmanouil; Hall, Marcia (Cells, 2019)
:Background: Current diagnosis and staging of advanced epithelial ovarian cancer (aEOC) has important limitations and better biomarkers are needed. We investigate the performance of non-haematopoietic circulating cells (CCs) at the time of disease presentation and relapse. Methods: Venous blood was collected prospectively from 37 aEOC patients and 39 volunteers. CCs were evaluated using ImageStream TechnologyTM and specific antibodies to differentiate epithelial cells from haematopoetic cells. qRT-PCR from whole blood of relapsed aEOC patients was carried out for biomarker discovery. Results: Significant numbers of CCs (CK+/WT1+/CD45-) were identified, quantified and characterised from aEOC patients compared to volunteers. CCs are abundant in women with newly diagnosed aEOC, prior to any treatment. Evaluation of RNA from the CCs in relapsed aEOC patients (n = 5) against a 79-gene panel revealed several differentially expressed genes compared to volunteers (n = 14). Size differentiation of CCs versus CD45+ haematopoietic cells was not reliable. Conclusion: CCs of non-haematopoetic origin are prevalent, particularly in patients with newly diagnosed aEOC. Exploiting a CC-rich population in aEOC patients offers insights into a part of the circulating microenvironment.
Keywords: nádory vaječníků; Female; Cell Line, Tumor; Neoplastic Cells, Circulating; ženské pohlaví; lidé; Ovarian Neoplasms; circulating tumour cells; Carcinoma; WT1 Proteins; karcinom; nádorové cirkulující buňky; circulating endothelial cells; nádorové biomarkery; Leukocyte Common Antigens; proteiny WT1; Biomarkers, Tumor; lidé středního věku; advanced epithelial ovarian cancer; Middle Aged; antigeny CD45; nádorové buněčné linie; Humans